Number 31 (April 1995) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1995)
(April 1995) - Nocturnal Reproductive Behavior in Semotilus atromaculatus (Pisces, Cyprinidae). By E.G. Maurakis, et al., 3 pp. Techniques of Videotaping Fishes From Above the Surface of the Water. By E.G. Maurakis and W.S. Woolcott, 3 pp. The Effect of Preservation on Urogenital Papilla Length in the Least Brook Lamprey Lampetra aepyptera. By P.A. Cochran and M.E. Sneen, 3 pp. Museum Notes by H.L. Bart and M.S. Taylor; Regional Reports.
Keywords: semotilus atromaculatus; pisces; cyprinidae; fishes; reproductive; nocturnal; videotaping; urogenital papilla; least brook lamprey; lampetra aepyptera